Knowledge and perceptions on end-of-life care among end-stage renal disease patients on hemodialysis - Rozi, Nur Raziana; Wan Ali, Wan Ahmad Syahril Rozli; Draman, Che Rosle; Pasi, Hafizah; Rathor, Mohammad Yousuf (Wolters Kluwer Medknow Publications, 2022)
The role of end-of-life care is fundamental for end-stage renal disease (ESRD) patients, who are known to have a high morbidity and mortality rate despite being on dialysis. This requires effective communication and shared decision-making. Thus, exploring patients’ knowledge and perceptions is essential to improve the gaps in delivering end-of-life care. This study aimed to describe the knowledge and perceptions of end-of-life care among ESRD patients on hemodialysis (HD). This was a cross-sectional study involving 14 outpatient HD centers in Kuantan, Malaysia. Patients were recruited from March to June 2019. A validated questionnaire was delivered via interview-based surveys by the researcher or trained interviewers. The majority of the respondents had poor knowledge of the disease and end-of-life care. However, more than 70% of the respondents felt that it was important for them to be actively involved in medical decision-making, as well as being prepared and planning for death. End-of-life needs, which included management of symptoms and psychological, social, and spiritual support, were important to most respondents. Additionally, patients with higher educational backgrounds were observed to have higher scores for both knowledge and perceptions (P <0.05). The study found poor knowledge but acceptable perceptions among patients. This highlights the gaps in the current local approach in clinical practice to end-of-life care in ESRD.